Identification of triterpenoid saponin inhibitors of interleukin (IL)-33 signaling from the roots of Astragalus membranaceus. (February 2023) - Vinh, Le Ba; Han, Yoo Kyong; Park, Si Young; Kim, Young Jun; Phong, Nguyen Viet; Kim, Eunji; Ahn, Bong-geun; Jung, Yong Woo; Byun, Youngjoo; Jeon, Young Ho; Lee, Ki Yong
Graphical abstract: Highlights: Eights compounds were isolated from Astragalus membranaceus, following bioassay-guided . Their structures were determined by spectroscopic methods. The molecular docking and molecular dynamic simulations of two active compounds supported the in vitro results. These results suggest that triterpenoid saponins from A. membranaceus roots might be useful for their pharmacological anti-allergic effects. Abstract: Interleukin-33 (IL-33) is a cytokine produced by epithelial cells that plays a key role in immune-mediated diseases, such as asthma, atopic dermatitis, and rheumatoid arthritis. In our research on the anti-allergic effects of Korean medicinal plants, we found that an ethanol extract from the roots of Astragalus membranaceus exhibited a significant IL-33 inhibitory effect. Using various chromatographic separation methods, eight compounds (1 –8 ) were isolated from the extract. The inhibitory effect of the isolated compounds on the IL-33 protein was also investigated by ELISA. Compounds 1, 5, and 6 showed significant IL-33 inhibitory activity. Moreover, molecular docking and molecular dynamic simulations of two active compounds supported the in vitro results. Taken together, these results suggest that triterpenoid saponins from A. membranaceus roots might be useful for their pharmacological anti-allergic effects.